Pattern of alcohol use among patients with traumatic brain injury in Malaysia's urban hospital / Lim Sze Huei - Lim, Sze Huei (2018)
Objective: To date, there is limited literature on the alcohol use among the patients with Traumatic Brain Injury (TBI) in Malaysia. Hence, the primary objective of the study is to determine the pattern of alcohol use among patients with traumatic brain injury in an urban hospital in Malaysia. The secondary objective is to investigate the association of alcohol use in the traumatic brain injured subjects with socio-demographic characteristics, duration of head injury and severity of head injury, history of alcohol use/substance use, psychological wellbeing, and cognitive function. Method: This is a cross sectional study conducted in the UMMC Rehabilitation Clinic, Neurosurgical clinic and ward, HKL Neurosurgical clinic and ward, the observation ward, Emergency Department. Data collection occurred from November 2017 till January 2018. A convenient sampling method was used. The patients were selected based on the selection criteria. The socio-demographic and clinical information were gathered after obtaining the informed consent from the patients or their guardians. The participants were each given a booklet of questionnaires to be filled which include their demographic particulars, alcohol use pre-or post TBI particulars, head injury particulars, AUDIT form, GHQ-12 form and MOCA form. All the questions were mainly in the Malay language and the researcher assisted the patients if the subjects had difficulties to understand the questions. 6 Results: Out of the 60 patients approached, only 47 patients were included in the study. The mean age of the participants was 36.8 years- (SD±14.8). In 83% of the patients were male (n=39) and females constituted 17% (n=8). The majority of the patients were Malays (63.8%) followed by Indian (23.4%) and Chinese (10.6%). In 51.1% of the participants were married and 48.9% were single or divorced. About two third of patients attained at least secondary education. Almost half of the patients (44.7%) were unemployed. Their average salary was RM 1429.79 (SD± 2340.28) A quarter of the subjects had used alcohol prior to their injury. There were significant associations between post-TBI alcohol use, an AUDIT score of 8 or more (OR 30, 95%CI 3.06-294.56) and alcohol use history (OR 1.31, 95%CI 1.03-1.67). A significant relationship was also noted between pre-TBI alcohol use and safety measure taken (OR 9.6, 95% CI 1.27-72.53). However, no significant associations were found between pre-TBI alcohol use with Modified Rankin Scale (mRS), neurosurgical intervention and GCS severity. Similarly, there was no significant associations were found between post-TBI alcohol use with age group, gender, marital status, educational status, occupation status, head injury duration, family history of alcohol use, pre TBI nicotine use, GHQ-12 score and MoCA score. Conclusion: The association with alcohol use and occurrence TBI is a complicated yet significant situation. Alcohol use affect incidence and subsequent recuperation from a TBI episode. The findings from the study, support the associations found in numerous literature; that the patients’ alcohol use pre-injury may contribute to their recovery and post-TBI usage. The findings of the study add evidence to the need to monitor alcohol level in all patients presenting with traumatic head injury.